2010
DOI: 10.1155/2010/543926
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofAgaricus blazeiMurill on the Pulmonary Tissue of Animals with Streptozotocin-Induced Diabetes

Abstract: The present study was designed to evaluate the oxidative stress as well as the therapeutic effect of Agaricus blazei Muril (A. Blazei) in rats with streptozotocin-induced diabetes. We used 25 Wistar rats, and DM was induced by injecting streptozotocin (70 mg/Kg i.p.). Agaricus blazei Muril was administered daily starting 40 days after disease onset. A. Blazei was tested as an aqueous extract for its phytochemical composition, and its antioxidant activity in vitro was also evaluated. Lipoperoxidation (LPO), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
1
13
0
4
Order By: Relevance
“…Increased levels of TBARS, an end-product of lipoperoxidation, were found previously in the liver of streptozotocin-induced diabetic rats [3941]. In this study, the TBARS increase confirms this finding, which indicates an overall oxidative stress increase in diabetic rats.…”
Section: Discussionsupporting
confidence: 91%
“…Increased levels of TBARS, an end-product of lipoperoxidation, were found previously in the liver of streptozotocin-induced diabetic rats [3941]. In this study, the TBARS increase confirms this finding, which indicates an overall oxidative stress increase in diabetic rats.…”
Section: Discussionsupporting
confidence: 91%
“…As NO and superoxide can react simultaneously to produce peroxynitrite that is very damaging [ 64 ], any evidence that NO concentration is elevated in the diabetic lung would suggest that NO/peroxynitrite pathway is a mechanism by which lung is injured. The pulmonary lipid peroxidation, glutathione peroxidase activities and inducible nitric oxide synthase (iNOS) were all found to be increased in streptozotocin diabetic rats [ 65 ]. Immunohistochemical staining in the pulmonary bronchial epithelium and capillary endothelium in the DM group indicates an elevated level of iNOS expression [ 65 ].…”
Section: Etiopathogenesis Of Diabetic Lung Injurymentioning
confidence: 99%
“…Also, it has been shown that dietary supplementation with natural antioxidants such as vitamins C and E, melatonin and flavonoids attenuates the oxidative stress and diabetic state induced by STZ 24,25 . The present study evaluates the in-vivo antioxidant activity of S. pinnata extract in diabetic rats Increased concentration of malonaldehyde, an endproduct of lipid peroxidation, were found in the liver homogenates of streptozotocin-induced diabetic rats 26,27 . In this study, the increase confirms this finding, which indicates an overall increase in oxidative stress in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%